Penggunaan Aplikasi Parafrasa untuk Menurunkan Plagiarisme pada Mahasiswa FKIP Universitas Asahan dalam Menyelesaikan Skripsi - Khairun Nisa; Ely Syafitri; Sri Rahma Dewi Saragih; Yen Aryni; Elfira Rahmadani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Paraphrasing must be done in writing scientific papers to avoid plagiarism. So this is important for all students. However, in reality, Asahan University FKIP students still have not mastered the correct paraphrasing technique. These abilities can be developed by diligently reading or with the help of free or paid online applications. The method of this activity was carried out in three stages, namely: preparation, implementation, and evaluation, by distributing questionnaires for student responses to the activities that have been carried out. This community service activity was at the Asahan University FKIP, Jalan Jend. Ahmad Yani Kisaran. Participants in this activity were all students of the seventh semester of the English Education study program, totalling 43 students, and Mathematics Education, totalling 57 students. This activity was carried out by introducing paraphrasing tools to help students reduce plagiarism. However, these tools must be re-read by students so that the meaning of the articles quoted is the same. The results of the introduction and training on paraphrasing applications, namely smodin, spinner id, quilbolt, and paraphrasing tools, were fascinating and help students reduce plagiarism. Based on the results of the evaluation through the distribution of google form questionnaires, it was found that 82% of students stated that the activities of using paraphrasing applications that were taught were beneficial. In comparison, 18% of students stated that it was helpful.